Recombinant BCG With Bacterial Signaling Molecule Cyclic di-AMP as Endogenous Adjuvant Induces Elevated Immune Responses After Mycobacterium tuberculosis Infection - Ning, Huanhuan; Wang, Lifei; Zhou, Jie; Lu, Yanzhi; Kang, Jian; Ding, Tianbing; Shen, Lixin; Xu, Zhikai; Bai, Yinlan (Frontiers in Immunology, 2019)
Bacillus Calmette-Guerin (BCG) is a live attenuated vaccine against tuberculosis (TB) and remains the most commonly used vaccine worldwide. However, BCG has varied protective efficiency in adults and has safety concerns in immunocompromised population. Thus effective vaccines are necessary for preventing the prevalence of TB. Cyclic di-AMP (c-di-AMP) is a bacterial second messenger which regulates various cellular processes and host immune response. Previous work found that c-di-AMP regulates bacterial physiological function, pathogenicity and host type I IFN response. In this study, we constructed a recombinant BCG (rBCG) by overexpressing DisA, the diadenylate cyclase of Mycobacterium tuberculosis (Mtb), and observed the physiological changes of rBCG-DisA. The immunological characteristics of rBCG-DisA were investigated on humoral and cellar immune responses in a mice infection model. Our study demonstrated that overexpression of DisA in BCG does not affect the growth but reduces the length of BCG. rBCG-DisA-immunized mice show similar humoral and cellar immune responses in BCG-immunized mice. After Mtb infection, the splenic lymphocytes from both BCG and rBCG-DisA-immunized mice produced more IFN-γ, IL-2, and IL-10 than the un-immunized (UN) mice, while the cytokine levels of the rBCG-DisA group increased significantly than those of the BCG group. The transcription of IFN-β, IL-1β and autophagy related genes (Atgs) were up-regulated in macrophages after treated with c-di-AMP or bacterial infection. The productions of IL-6 were increased after Mtb challenge, especially in the rBCG-DisA-immunized mice. Strikingly, H3K4me4, the epigenetic marker of innate immune memory, was found in both two immunized groups, and the rBCG-DisA group showed stronger expression of H3K4me4 than that of BCG. In addition, the pathological changes of rBCG-DisA immunized mice were similar to that of BCG-immunized mice. The bacterial burdens in the lungs and spleens of BCG- and rBCG-DisA-immunized mice were significantly decreased, but there was no significant difference between the two immunized groups. Together, these results suggested that compared to BCG, rBCG-DisA vaccination, induces stronger immune responses but did not provided additional protection against Mtb infection in this study, which may be related to the innate immunity memory. Hence, c-di-AMP is a promising immunomodulator for a further developed BCG as a better vaccine.